KISSAT'U SÜLEYMAN FI'T-TECRÂT'I VE'L-KUR'ÂN (TEVRAT'TA VE KUR'AN'DA HZ. SÜLEYMAN KISSASI) - ABUBAKER, JALIL IBRAHIM ABUBAKER (Fırat Üniveristesi, 2021)
Bu çalışma, Tevrat ve Kur'an-ı Kerim'deki verileri esas almak suretiyle Hz. Süleyman'ın kıssasını ele almaktadır. Benzer ve farklı yönleriyle kıssa'nın gözler önüne serilebilmesi için öncelikle her iki kaynaktaki ilgili ayetler tespit edilmiştir. Bunun yanında gerek Tevrat gerekse de Kur'ân müfessrilerinin bu husustaki görüşlerine başvurulmuştur. Bir kaynakta bulunup diğerinde bulunmayan hususlar büyük oranda araştırmanın dışında bırakılmıştır. Çalışmada Süleyman kıssasına ilişkin her iki kaynakta yer alan ortak malumat sadece karşılaştırmalı olarak incelenmemiş, mevcut Tevrat ve Kurân anlatımları yer yer iç tutarlılık açısından da değerlendirilmiştir. Bu çerçevede Hz. Süleyman'ın peygamberliği, krallığı, dini tutum ve davranışları, kendisine bahşedilen ilahi nimetler, Sebe melikesi Belkıs'la ilişkisi, sihir ve cinlerle irtibatı ve vefatı gibi konulara yer verilmiştir.

This study talks about the story of the Prophet of God Solomon, peace be upon him, as told by the Torah and the Noble Qur'an. The whole story was presented as it came in the two sources. It mentioned all the texts and verses related to the topic, with reference to the views of the most famous commentators, then compared and discussed them and commented on the views of their commentators, and mentioned similarities. And the difference between them, as the Noble Qur'an mentioned some issues and elaborated on them, while the Torah rejected it and did not mention it, and vice versa as well. In the first topic: We touched upon that God Almighty made him the heir of his father in prophethood and the caliphate, and that he sat on his father's chair, and we also mentioned his worship, his abundance of veneration, wisdom, his judgment, his virtue, and the use of his property to please God Almighty and jihad in his path, and that God Almighty gave him from the extraordinary habits and apparent miracles. And in the second topic: We mentioned the miracles of his king, building cities, trade and industry, and we shed light on the things that were ridiculed for him by no one after him, such as the wind, demons, jinn and the dropping of the eye of the country to him. As for the third topic, we dealt with his story with Queen Belqis, which is the closest story to the similarity between the Torah and the Holy Qur'an. In the fourth topic: We mentioned how he died, along with the issues related to it from magic, the unseen jinn claim, and so on.
The Story of Solomon in The Torah and The Quran
Keywords: Din